Solitude seeking wisdom in extremes ; a year alone in the Patagonia wilderness - Kull, Robert 1946- (Novato, Calif. New World Library, 2008)
On journaling and storytelling -- Methodology, solitude, and meditation -- Other solitaries -- The urge to be alone -- Dancing in the hallowed halls -- Technology and desire -- Spiritual practice -- Small mind/big mind, dark/light
On journaling and storytelling -- Methodology, solitude, and meditation -- Other solitaries -- The urge to be alone -- Dancing in the hallowed halls -- Technology and desire -- Spiritual practice -- Small mind/big mind, dark/light.
Includes bibliographical references (p.351-354)
Archivierung prüfen
Keywords: Kull -- Robert -- Travel -- Patagonia (Argentina and Chile); Solitude; Spiritual Life; Wilderness areas -- Patagonia (Argentina and Chile) -- Description and travel; Patagonia (Argentina and Chile) -- Description and travel; Reisebericht